Expression of resistance to Xanthomonas campestris pv. phaseoli in Phaseolus vulgaris under tropical conditions - Webster, DM; Temple, Steven R.; Galvez, G (Scientific Societies, 1983)
The bean (Phaseolus vulgaris) cultivar Jules and the PI 207262 line are moderately resistant to Xanthomonas campestris pv. phaseoli in the temperate zone but appeared susceptible in field evaluations in the tropics. Susceptibility to the pathogen was related to environmental factors that caused very early maturity and poor growth; blight resistance was expressed relative to controls when these factors were altered to permit more normal growth of Jules and PI 207262. The effect of environmental factors on resistance to common blight was observed in evaluations made at 44 and 55 days after planting but not at 34 days.